External Debt, Debt Service and Economic Growth: Empirical Evidence from the ECOWAS Sub-Region - Ashakah, Felix Onoriode; Irogbo, Prosper Uyoyou; Ezeh, Matthew Chinedum; Owhe-Ureghe, Augustine Othuke; Igben, Harvest; Opara, Festus Ndidi (International Journal of Economics and Financial Issues, 2024)
The paper investigated the impact of external debt, and debt service on economic growth in the ECOWAS sub-region during the period 1990 to 2022. The study analyzed a panel data set using the fixed and random effect models. The results of the panel data unit root test confirmed that the variables in the specified model were integrated in different orders. The panel co-integration tests indicated that a long-run relationship existed among the variables in the specified debt-growth model. The results of the model estimation revealed that external debt negatively and significantly impacted economic growth at the 1% level during the period of the study. The results further revealed that debt service negatively impacted economic growth, but failed the significance test at the 5% level. The paper recommended that countries in the ECOWAS sub-region should reduce external debt accumulation, and efficiently use revenue generated from external debt to boost economic growth.